ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROSES PENDISTRIBUSIAN OBAT DAN ALAT KESEHATAN DARI GUDANG FARMASI KE INSTALASI RAWAT INAP DI RSU GMIM BETHESDA TOMOHON - Matius Herwanto (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Hospital should have a professional human resources, both in medical technical field and health administration, so hospital services could be safe and have a good quality. The hospital pharmacy service system is a system that cannot be separated from the hospital health service system, both oriented to patient care and the provision of pharmaceutical logistics. inefficient services can result in losses for the hospital and for the patients themselves. Therefore, in the selection of a drug service system, it must be selected and adapted to existing conditions, so the drug services can be carried out in an effective and efficient way.The purpose of this study was to identify and analyze the factors that influence the distribution of drugs and medical devices from pharmacy warehouses to inpatient installations at RSU GMIM Bethesda Tomohon. This type of research is descriptive, that using a qualitative approach. The samples were pharmacists, nurses, doctors, and patients with a total of 12 people. The data were analyzed using the content analysis method on the interview results.The results of the study from the factors that supporting the distribution of drugs at GMIM Bethesda Tomohon Hospital were in the application of the unit dose dispensing system used. This system can minimize medication dispensing errors and control the hospital pharmacy installation which has a wider scope, starting from the doctor writing the prescription/order until the patient receives the unit dose. The inhibiting factors are in the form of centralization that is not supported, the position of the pharmacy installation, the installation that serves both outpatients and inpatients simultaneously, the lack of pharmacy workers, drug vacancies, storage warehouse area, doctor's writings and visiting hours.The conclusion of this study is that there are factors that support and hinder the distribution of drugs and medical devices from pharmacy warehouses to inpatient installations at RSU GMIM Bethesda Tomohon.